2008
DOI: 10.1152/ajprenal.00308.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid type 1 channels act as mechanoreceptors and cause substance P release and sensory activation in rat kidneys

Abstract: Stimulation of capsaicin receptors results in an increase in afferent renal nerve activity (ARNA), but it is unclear how capsaicin contributes to sensory activation intrarenally. Here, we studied the relationships between capsaicin receptor activation, substance P (SP) release, and the sensory response in the rat renal pelvis. Immunoblots showed that one of the capsaicin receptors, transient receptor potential vanilloid type 1 channel (TRPV1), was found in various renal tissues and was especially abundant in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 40 publications
3
66
1
Order By: Relevance
“…It has been demonstrated most recently that TRPV1 protein is highly present in the renal pelvis and exclusively regulates neuropeptide release from primary renal afferent nerves in response to mechanostimulation [19]. Moreover, TRPV1 protein is abundantly located in renal tubules of medulla, although its functional roles are unknown [19]. The renal medulla contains nephron segments that are most susceptible to ischemic injury [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated most recently that TRPV1 protein is highly present in the renal pelvis and exclusively regulates neuropeptide release from primary renal afferent nerves in response to mechanostimulation [19]. Moreover, TRPV1 protein is abundantly located in renal tubules of medulla, although its functional roles are unknown [19]. The renal medulla contains nephron segments that are most susceptible to ischemic injury [20].…”
Section: Introductionmentioning
confidence: 99%
“…3 The reason for the absence of NMDA1 mRNA is not known. However, Washbourne et al 24 showed that NMDAR subunits are present in mobile transport packets and move rapidly along microtubules to axodendritic sites during synaptogenesis in rat cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 Western blotting was performed using antibodies (Santa Cruz) against rat NMDA1 (1:1000), serine racemase (SR) (1:1000), or actin (1:2000) as described previously. 3,8 -10 The negative control was staining with primary antibody preincubated with specific blocking peptide (Santa Cruz).…”
Section: Detection Of Nmda1 and Serine Racemase In Renal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations